Wood-Based Solar Interfacial Evaporator for Efficient Seawater Desalination Processed by Picosecond Laser - Chu, Dongkai (Langmuir : the ACS journal of surfaces and colloids, 2025)
With the continuous growth of the global population and the acceleration of industrialization and urbanization, freshwater scarcity has become an increasingly severe challenge. Solar-powered seawater desalination technologies based on interfacial evaporators have received widespread attention. However, the preparation process of interfacial evaporators is complicated, and it is difficult for them to maintain long-term service. Here, a simple method for fabricating solar interfacial evaporators using picosecond laser of wood-based materials is proposed. The surface of the wood-based material after laser processing exhibits excellent antireflective properties. The average reflectance within the spectral range of 200 to 2500 nm is 18.04%, which has been reduced by 40.14% compared to the original surface. The as-prepared interfacial evaporator has a high-water evaporation rate of ∼3.58 kg m-2 h-1 and a solar steam efficiency of ∼92.85% under one sun irradiation during the indoor testing. The outdoor seawater desalination efficiency can reach 1.95 kg m-2 h-1. After desalination, the concentrations of five major ions, namely Na+, Mg2+, Ca2+, K+, and B3+, meet the ion concentration standards for drinking water set by the WHO. This research offers a rapid, cost-effective, and efficient method for seawater desalination, providing a promising solution to freshwater scarcity